Performance enhancement of audio transmission based on LMMSE method - Marwa Al-Sultani; Haraa Raheem Hatem; Wurod Qasim Mohamed (Institute of Advanced Engineering and Science, 2021)
The research in wireless communication has developed rapidly for the last decades as a result of raising the demand for efficient data transmission with more security and accuracy. This paper proposed a system based on the special multiplexing (SM) technique and linear minimum mean square error (LMMSE) detection method with the assistance of the hamming code as well as the interleaving techniques for a better enhanced performance of an audio transmission. Moreover, the comparison was done between the two systems for different antenna configurations and with the presence of two types of modulation: binary phase shift key and quateradure phase shift key. These systems are employed by Matlab simulation to show significant results in terms of enhancing the Rayleigh fading channel capacity, bit error rate (BER) and security as well as in recovering the transmitting audio signals. Each system has advantages than the others in one performance term respect to the other terms. The Simulation results have provided to prove and discuss our analysis.